Restorative Justice Evaluation: The Impact of Structural Inequities in the Criminal Justice System - Devi Ratnasari; Fazhri Surachman; Gunadi Rasta; Diky dikrurahman (PT Publikasiku Academic Solution, 2025)
Structural inequality poses a persistent challenge within the criminal justice system, shaped by social factors such as poverty, race, and gender. Restorative justice offers an alternative to retributive models by emphasizing the restoration of relationships through inclusive dialogue among victims, offenders, and communities. This study evaluates the effectiveness of restorative justice in addressing structural inequality, utilizing qualitative methods including literature analysis and case studies from various countries, such as Indonesia. The analysis draws on academic journals, policy reports, and legal documents, alongside practical examples of restorative justice implementation. Findings suggest that restorative justice can promote a more inclusive justice system by empowering both victims and offenders and facilitating community involvement. However, challenges persist, including institutional bias, resource limitations, and resistance from the conventional justice system. To enhance the effectiveness of restorative justice, the study recommends institutional reforms, context-sensitive mediator training, and increased policy and resource support. Furthermore, fostering synergy between formal legal mechanisms and local, community-based approaches is crucial for addressing the root causes of structural inequalities. Overall, while restorative justice demonstrates significant potential, its success depends on overcoming systemic barriers and ensuring sustained commitment from all stakeholders.